Algebra, Solving equations

posted by .

I'm stuck with this equation:

y = (4x-1)/(2x+3)

We're working on inverses, which I understand, but my mind is blanking on how to solve this for x.

Thanks in advance,
Amy :)

after you interchanged the x and y variables, and expanded you should have had
x = 8y^2 + 10y - 3

arrange to look like a quadratic equation
8y^2 + 10y - 3 - x = 0

now a=8, b=10 and c=-3-x

use the formula to solve for y

notice you get 2 different equations.
Are you also learning about functions?

Oh, this is embarassing...I'm studying inverse functions in calculus and I'm getting hung up on algebra I did in high school. :)

This particular problem's directions say to find the inverse of the given function, but I thought I read that if it's not a one-to-one function, it doesn't have an inverse. So if there's two equations once I use the quadratic formula, then this equation doesn't have an inverse, right?


Hold on a sec...There's division between those two terms, so I wouldn't end up getting two different answers, right?

I got y = (-10 + sqrt(100-32(-3-x)))/16 for one and
y = (-10 - sqrt(100-32(-3-x)))/16 for the other, thus 2 distinct equations

recall that taking the inverse of a relation results in a reflection in the line y=x
Your original equation was a parabola opening upwards, so its inverse is a parabola with axis parallel to the x-axis.

so for a given value of x (in the new domain) you now have 2 different values of y, making it NOT a function.

Do you recall something called the "vertical line test" ?

But it's division. I'm dividing (4x-1) by (2x+3). I guess my main question is how do I simplify the original equation so that I can solve it for x. I know I can't just factor it because there's no common factors. When I graph the equation on my calculator, it passes both the VLT and the HLT, so it's definitely one-to-one.

oops, oops, oops, my mistake, lets back up
I read that as a multiplication, sorry

now it's actually easier:

step 1 of finding inverse: interchange the x and y variables...

y = (4x-1)/(2x+3) turns into x = (4y-1)(/2y+3)

cross multiply
2xy+3x=4y-1
2xy-4y=-1-3x or
4y-2xy = 1+3x
y(4-2x) = 1+3x
y = (1+3x)/(4-2x)

now clearly the original was a function and so is the new one.

test (-1,-5) in original and (-5,-1) in new one

Thanks. I was getting so confused!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    can someone correct these for me. 8x –4y = 16 y = 2x –4 My answer: This problem does not have a unique solution. This problem therefore is consistent and dependent These equations are the same. If you solve the first one for y, …
  2. Engineering

    I need help solving the following simultaneous equations, for the values of Vo and a: 1.4 = Vo e^-32a 4 = Vo e^-6a I've never come across simultaneous equations like this (e is the base of natural logarithms, so perhaps taking logs …
  3. math-rational equations

    how do I solve 5/x-3+3/x+3=7x/x^2-9 please explain in detail, I am having trouble once I get to the part where I need to simplify. I have so far the LCD is x^2-9 then the equation changes to (x^2-9) 5/x-3+(x^2-9) 3/x+3=(x^2-9) 7x/x^2-9 …
  4. FOR MATHMATE

    Media services charges $40 for a phone and 20/mth for its economy plan. It says to find a model that determines the total cost, C(t), of operationg a media Services phone for t months. I think the answer should be in this equation …
  5. Math

    Solve each equation write answer on simplest form 1/4x = 6 2t = 4/7 Can you show me how to do didn't understand on class. Working on solving fraction equation. Multiply and divide
  6. Algebra

    I don't quite understand how to solve matrices with three variables. If I have the equations: 7x-4y-2z=0 2x-3y+z=-0.25 -2x-2y+5z=0 How can I solve this?
  7. Algebra

    Solving equations simultaneously: .7*x+.30*y=33.1 (x*y)/(.7*y+.30*x) = 3.66 I get stuck after I get 51.972=45.2y-.42y^2 I know the answers are supposed to be x=2.6 and y=104
  8. Algebra SOLVING LINEAR EQUATIONS AND INEQUALITIES

    Please help Im am Grade 5 and my teacher is letting me do this. 1. Solve the solution by using elimination and substitution 3/x - 2/y = 14 6/x + 3/y = 7 2. Solve by eliminating x (this is solving 3 linear equations) then substitute …
  9. Algebra I DONT KNOW HOW TO DO 3 VARIABLES

    Solving Linear Equations and Inequalities Solve by eliminating x (this is solving 3 linear equations) then substitute to the other two equation x + y + 5z =2 (1) 4x - 3y + 5z =3 (2) 3x - 2y + 5z=1 (3) my teacher gave me the answer …
  10. Algebra

    Solving Linear Equations and Inequalities Solve by eliminating x (this is solving 3 linear equations) then substitute to the other two equation x + y + 5z =2 (1) 4x - 3y + 5z =3 (2) 3x - 2y + 5z=1 (3) my teacher gave me the answer …

More Similar Questions